Between Tradition and Modernization: Attitudes Toward Women's Employment and Gender Roles in Croatia - Brajdić Vuković, Marija (Array, 2007)
Despite the fact that state socialism promoted the employment of women and, at least formally, gender equality as means of societal modernization, the prevailing picture of the Southeast European region is one of rather traditional, patriarchic societies. The postcommunist transition was characterized by high social costs and political attempts at retraditionalization, particularly through the increasingly public role of religion. At the same time, the societies were under more universal influence of modernity processes of individualization and permissiveness. Thus, it is difficult to assess in which direction, toward modernity or traditionalism, these societies are heading. In this article we analyze attitudes toward gender roles and women’ s employment in Croatia. Using the South-East European Social Survey Project (SEESSP) data set (2003), we test several hypotheses linking respondents’ attitudes with their socioeconomic characteristics as well as their upbringing. Our analyses have implications for gender policy in transitional economies that are burdened by consistently high unemployment rates, particularly among women, and by frequent, politically motivated, attempts at retraditionalization.